2011
DOI: 10.1128/jcm.00467-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single-Tube Multiplex Real-Time PCR for Differentiation of Members of the Mycobacterium tuberculosis Complex in Clinical Specimens

Abstract: Members of the M. microti, M. canettii, M. caprae, M. pinnipedii, and M. mungi (1). Differentiation between the species within this complex is important for public health surveillance and reference testing, as most species within the MTBC have been reported to infect humans (6). Additionally, it may be important information for physicians to rapidly identify severe side effects of M. bovis BCG in patients with bladder cancer or in vaccinated individuals or to assess transmission of M. bovis from animals or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 20 publications
1
72
0
1
Order By: Relevance
“…The primers and the probe are listed in Table 2. Nucleotide sequence data for the primers and the probe were deduced from various reports (14,16,18,26,33) or were generated in this study using the NCBI/Primer-BLAST program (http://www.ncbi.nlm.nih .gov/tools/primer-blast/index.cgi?LINK_LOCϭBlastHome) based on the sequences derived from whole-genome sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primers and the probe are listed in Table 2. Nucleotide sequence data for the primers and the probe were deduced from various reports (14,16,18,26,33) or were generated in this study using the NCBI/Primer-BLAST program (http://www.ncbi.nlm.nih .gov/tools/primer-blast/index.cgi?LINK_LOCϭBlastHome) based on the sequences derived from whole-genome sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Rodriguez et al (8) confirmed the existence of 545-bp RD4-specific sequences in 62 of 63 M. caprae isolates. Notably, the detection of an RD4 deletion has been used as a major criterion for distinguishing M. bovis from the other members of the MTC, especially from M. caprae (16)(17)(18)(19)(20)(21).One M. caprae-specific T-to-G substitution at position 1311 in the gyrB sequence has been described in several M. caprae isolates from central Europe (12,22,23) and Spain (3,8). However, Kubica et al (24) reported that 3 of 55 German M. caprae isolates from human patients did not show this M. caprae-specific SNP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Desde el punto de vista bioquímico, lo inhibe la hidracida del ácido tiofeno-2-carboxílico, muestra fuerte actividad ureasa y es resistente a pirazinamida y a cicloserina (esto último lo diferencia del M. bovis común). Aunque ya hay descritas en la literatura especializada algunas técnicas para desmembrar el complejo [18][19][20] , no hay muchas pruebas comercializadas, siendo éste un aspecto de una gran importancia clínica y epidemiológica. Para la identificación de la especie causante de la infección del presente caso se realizó una técnica de amplificación de ácidos nucleicos casera.…”
Section: Discussionunclassified
“…Unlike PCR assays previously mentioned for differentiation of members of Mtb complex, a real-time PCR assay, developed by Halse and colleagues (Halse et al, 2011) …”
Section: Laboratory-developed Pcr Methodsmentioning
confidence: 99%